Radiation Dose Escalation or Longer Androgen Suppression to Prevent Distant Progression in Men With Locally Advanced Prostate Cancer: 10-Year Data From the TROG 03.04 RADAR Trial - Joseph, David; Denham, James W; Steigler, Allison; Lamb, David S; Spry, Nigel A; Stanley, John; Shannon, Tom; Duchesne, Gillian; Atkinson, Chris; Matthews, John H L; Turner, Sandra; Kenny, Lizbeth; et al. (International journal of radiation oncology, biology, physics, 2020)
To clarify the relative effects of duration of androgen suppression (AS) and radiation dose escalation (RDE) on distant progression (DP) in men with locally advanced prostate cancer. Participants with locally advanced prostate cancer in the TROG 03.04 RADAR trial were randomized to 6 or 18 months AS ± 18 months zoledronic acid (Z). The trial incorporated a RDE program by stratification at randomization and dosing options were 66, 70, or 74 Gy external beam radiation therapy (EBRT), or 46 Gy EBRT plus high-dose-rate brachytherapy boost (HDRB). The primary endpoint for this study was distant progression (DP). Secondary endpoints included local progression, bone progression, prostate cancer-specific mortality and all-cause mortality. Effect estimates for AS duration and RDE were derived using Fine and Gray competing risk models adjusting for use of Z, age, tumor stage, Gleason grade group, prostate-specific antigen, and treatment center. Cumulative incidence at 10 years was estimated for each RDE group. A total of 1051 out of 1071 randomized subjects were eligible for inclusion in this analysis. Compared with 6 months AS, 18 months AS significantly reduced DP independently of radiation dose (subhazard ratio 0.70; 95% confidence interval [CI], 0.56-0.87; P = .002). No statistically significant interaction between effect of AS duration and RT dose was observed (Wald test P = .76). In subgroup analyses, DP was significantly reduced by the longer duration of AS in the 70 Gy and HDRB groups but not in the 66 Gy and 74 Gy. Compared with 70 Gy, HDRB significantly reduced DP (subhazard ratio 0.68 [95% CI, 0.57-0.80]; P < .0001) independently of AS duration. At 10 years, adjusted cumulative incidences were 26.1% (95% CI, 18.9%-33.2%), 26.7% (22.9%-30.6%), 24.9% (20.0%-29.8%) and 19.7% (15.5%-23.8%) for DPs in the respective radiation dose groups. Compared with 6 months AS, 18 months AS reduced DP independently of radiation dose. Men treated with HDRB gained a significant benefit from a longer duration of AS. Evidence of improved oncologic outcomes for HDRB compared with dose-escalated EBRT needs to be confirmed in a randomized trial.